Thoracoscopic surgery for refractory cases of secondary spontaneous pneumothorax. Issue 2 (29th October 2012) - Odaka, Makoto; Akiba, Tadashi; Mori, Shohei; Asano, Hisatoshi; Yamashita, Makoto; Kamiya, Noriki; Morikawa, Toshiaki
Abstract Introduction Secondary spontaneous pneumothorax (SSP) can be life threatening because patients often have severe lung disease with other coexisting diseases such as heart disease. In this study, we evaluate the feasibility of thoracoscopic surgery to treat SSP and discuss thoracoscopic techniques for managing complicated cases. Methods We retrospectively evaluated the outcome of thoracoscopic surgeries in 21 SSP patients. Results Fifteen patients had chronic emphysema, four had interstitial pneumonia, and two had inflammatory lung disease. All patients presented with persistent air leaks, and their median preoperative hospital stay was 11 days. All patients underwent thoracoscopic surgery. In 12 patients, the leaking bullae were excised by endoscopic stapling. Fibrin glue was used in 16 cases and polyglycolic acid sheets in 17. Polyglycolic acid sheets and fibrin glue without bullectomy were used in three cases. Air leaks were treated by simple stapling in four cases and by gelatin‐resorcin formaldehyde glue in five. Median postoperative hospital stay was 8 days. No patients required conversion to open surgery. Postoperative complications such as persistent air leaks, pneumonia, and acute respiratory failure were observed in six patients. Four recurrences of pneumothorax were observed during the median postoperative follow‐up period of 19.3 months. Conclusion Our results suggest that thoracoscopic surgery is feasible and less invasive than open surgery for high‐risk patients, and it improves patient quality of life. Various techniques to stop air leaks enabled us to treat patients with refractory SSP.